A study on the effects of different organic fertilizers on the growth of Chlorella Vulgaris. - Tingson, Pedro Fanaga, Jr. (1980.)
Three farm manures namely: hog manure, chicken manure, and guano were assessed as to its effectiveness on the growth of the unicellular algae, Chlorella vulgaris. Algal yield was measured in terms of number of cells per cubic centimeter. Yield was note daily for nine days. Results indicated that the treatment with chicken manure generally showed high and consistent yield over the treatments with hog manure and guano. The experiment was terminated on the twelfth day when the death phase was noted.
Research Paper (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Chlorella Vulgaris